Measuring level of administrative transparency of sports federations heads and clubs in Qadisiyah governorate (From point of view of its employees) - Ali Kareem Finteel (Khatulistwa Education Center, 2026)
Background Research questions What is level of practicing transparency of legislation among heads of sports federations and clubs in province of Qadisiya? What is level of transparency of Information Systems practiced by heads of sports federations and clubs in Qadisiya governorate? What is level of practice of transparency of communications among heads of sports federations and clubs in province of Qadisiya? What is level of practicing transparency of decision-making among heads of sports federations and clubs in Qadisiyah governorate? What is level of transparency of administrative accountability practiced by heads of sports federations and clubs in Qadisiyah governorate? What is level of practicing transparency of performance evaluation among heads of sports federations and clubs in province of Qadisiya? Objectives Study aims to identify level of administrative transparency practice among heads of sports federations and clubs in Qadisiyah governorate. Methods Method used the researcher used descriptive survey method with his steps and procedures. Research community the researcher identified research community of employees of sports federations and clubs, which number(237) individuals. Research sample: research sample was selected randomly from employees of sports federations and clubs, and research sample amounted to (197) individuals with (40) individuals for survey sample and(197) individuals for basic sample. Results Research conclusions there is a clear definition of duties and responsibilities of all specialists in sports federations and clubs, according to a job description, job title and purpose of job are determined, and required responsibilities. Sports federations and clubs do not take into account potential of their specialists when issuing regulations by developing capabilities and skills of employees in order to achieve these required goals. Conclusion Research recommendations adopting and spreading culture of administrative transparency in all its variables to become a basic approach in work of sports federations and clubs. Strengthening commitment to principle of transparency in sports federations and clubs through organization of seminars and conferences on transparency practices.